Present status of undergraduate urological education in Turkey: Is standardization necessary? - (:unkn) unknown (My University, 1990)
23 medical faculties exist in Turkey at the moment and 2 others are being established. Considering that all these faculties run their own programs independently, different education systems might effect the standard of doctors and health care. All of the new graduates in this country face a centralized examination for postgraduate posts in teaching hospitals or start an obligatory service under the authority of the Ministry of Health and Social Welfare. This necessitates standardization in medical education to provide equal facilities and opportunities to all young doctors. Questionnaires, replied to by the urology departments of medical faculties, reflect a wide range of teaching periods in urology with a broad spectrum of topics. Under these circumstances it is advisory to agree on both the time period and content of a standard urology program, as well as other subjects, for better health care and equal chances in centralized examinations.
Keywords: Standardization; Urological education